2003
DOI: 10.1007/s00345-003-0351-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of endoscopic extraperitoneal radical prostatectomy (EERPE)?technical improvements and development of a nerve-sparing, potency-preserving approach

Abstract: During the last decade, laparoscopy has become a standard technique in the armoury of the urologist due to constant technological advances and refinements. Laparoscopic radical prostatectomy (LRPE), although technically demanding and associated with a considerable learning curve, has become the surgical procedure of choice in selected and specialized urological centers around the globe for patients with clinically localized prostate cancer. However, a major drawback of LRPE is the transperitoneal route of acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 17 publications
0
27
0
6
Order By: Relevance
“…It reduces the risks of damaging intraperitoneal organs, prolonged adynamic ileus, intracavitary tumor spread, as well as bleeding or urine extravasations into the peritoneal cavity. Some authors also believe that it allows better dissection of the neurovascular, as demonstrated in other series (14,15).…”
Section: Commentsmentioning
confidence: 89%
“…It reduces the risks of damaging intraperitoneal organs, prolonged adynamic ileus, intracavitary tumor spread, as well as bleeding or urine extravasations into the peritoneal cavity. Some authors also believe that it allows better dissection of the neurovascular, as demonstrated in other series (14,15).…”
Section: Commentsmentioning
confidence: 89%
“…Ya se ha descrito previamente la técnica inicial de PRETE [9][10][11] . Al aumentar nuestra experiencia en la realización de PRETE, pudimos desarrollar un planteamiento de conservación de nervios (PRETEcn) que aplicamos de forma habitual en pacientes seleccionados.…”
Section: La Técnicaunclassified
“…En 2003, publicamos los resultados obtenidos en los 70 primeros casos 10 . Desde entonces, hemos mejorado la técnica de forma continua, incluyendo la conservación de nervios para mantener la potencia sexual (PRETEcn) 11 . En este trabajo, presentamos la evolución de la téc-nica y los últimos resultados oncológicos y funcionales después de 700 procedimientos.…”
unclassified
“…Die Technik der EERPE wurde kontinuierlich weiterentwickelt, einschließ-lich der Entwicklung einer nerven-und potenzerhaltenden Operationstechnik (nEERPE). Sie wird mittlerweile standardisiert und als First-line-Therapie des lokal begrenzten Prostatakarzinoms eingesetzt [24,25].…”
Section: Präperitonealraumesunclassified